Non-local thermodynamic equilibrium spectral analysis of five hot, hydrogen-deficient pre-white dwarfs - Werner, Klaus; Reindl, Nicole; Dorsch, Matti; Geier, Stephan; Munari, Ulisse; Raddi, Roberto (Astronomy & Astrophysics, 2022)
Hot, compact, hydrogen-deficient pre-white dwarfs (pre-WDs) with effective temperatures of T-eff > 70 000 K and a surface gravity of 5.0 < log g < 7.0 are rather rare objects despite recent and ongoing surveys. It is believed that they are the outcome of either single star evolution (late helium-shell flash or late helium-core flash) or binary star evolution (double WD merger). Their study is interesting because the surface elemental abundances reflect the physics of thermonuclear flashes and merger events. Spectroscopically they are divided in three different classes, namely PG1159, O(He), or He-sdO. We present a spectroscopic analysis of five such stars that turned out to have atmospheric parameters in the range T-eff = 70 000-80 000 K and log g = 5.2-6.3. The three investigated He-sdOs have a relatively high hydrogen mass fraction (10%) that is unexplained by both single (He core flash) and binary evolution (He-WD merger) scenarios. The O(He) star JL 9 is probably a binary helium-WD merger, but its hydrogen content (6%) is also at odds with merger models. We found that RL 104 is the 'coolest' (T-eff = 80 000 K) member of the PG1159 class in a pre-WD stage. Its optical spectrum is remarkable because it exhibits C iv lines involving Rydberg states with principal quantum numbers up to n = 22. Its rather low mass (0.48(-0.02)(+0.03)M(circle dot)) is difficult to reconcile with the common evolutionary scenario for PG1159 stars due to it being the outcome of a (very) late He-shell flash. The same mass-problem faces a merger model of a close He-sdO plus CO WD binary that predicts PG1159-like abundances. Perhaps RL 104 originates from a very late He-shell flash in a CO/He WD formed by a merger of two low-mass He-WDs.
CRIS-Team WoS Importer:2022-02-11